2005
DOI: 10.1007/s10529-005-7179-3
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Recombinant Truncated Human Interleukin-11 Expressed as Fusion Protein in Escherichia coli

Abstract: Mature human interleukin-11 (HuIL-11) is a cytokine consisting of 178 amino acid residues that results from scission of the N-terminal signal peptide, consisting of 21 amino acid residaues, from the corresponding nascent polypeptide. A DNA fragment encoding a truncated HuIL-11 (trHuIL-11), with an additional 5 amino acid residues removed from the N-terminus, was cloned into vector pGEX-2T between the BamHI site and the EcoRI site. Upon transformation with Escherichia coli BL21, the construct over-produced a gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…The precursor protein contains 199 aas (MW=23 kDa), including a signal peptide sequence of 21 aas, which is cleaved off before releasing the protein from the cell [7]. IL-11 is very basic due to a high abundance of leucine (23%), proline (12%), and positively charged aas (14%) [4,8].…”
Section: Il-11 Characteristics and Structurementioning
confidence: 99%
See 3 more Smart Citations
“…The precursor protein contains 199 aas (MW=23 kDa), including a signal peptide sequence of 21 aas, which is cleaved off before releasing the protein from the cell [7]. IL-11 is very basic due to a high abundance of leucine (23%), proline (12%), and positively charged aas (14%) [4,8].…”
Section: Il-11 Characteristics and Structurementioning
confidence: 99%
“…Variations in the N-terminal region up to residue 60, compared to the other parts, are more frequent. In this context, results from several investigations suggested that the bioactivity of hIL-11 is mostly dependent on its C-terminal, while in some mutational studies using alanine scanning or a truncation method, the N-terminal was identified as an unstructured non-functional region [6,7,23,27]. Because an unstructured region usually brings susceptibility to proteolysis, the N-terminal part has been targeted for removal in attempts to obtain a more stable protein against chemical and proteolytic stresses.…”
Section: Il-11 Characteristics and Structurementioning
confidence: 99%
See 2 more Smart Citations
“…8. Interleukin 11, contrary to other cytokines such as hIL-6 or granulocyte colony-stimulating factor (45,46), is not glycosylated in its native form (47). Dissimilar glycosylation patterns among interleukins could contribute to the fascinating diversity of signaling events elicited by this structurally homologous family of cytokines.…”
Section: Non-core Region Modulates Hil-11mentioning
confidence: 99%